1989
DOI: 10.1109/23.45391
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between preirradiation 1/f noise and postirradiation oxide-trapped charge in MOS transistors

Abstract: We have performed a detailed comparison of the preirradiation l/f noise and the radiation-induced threshold voltage shifts due to oxide-trapped and interface-trapped charge, AVot and A&, for enhancement-mode, 3-pm gate, nchannel MOS transistors taken from seven different wafers processed in the same lot. These wafers were prepared with gate oxides of widely varying radiation hardness. We show that the preirradiation l/f noise levels of these devices correlate strongly with the postirradiation AVot, but not wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 31 publications
(16 reference statements)
4
19
1
Order By: Relevance
“…[8][9][10][11][12][13] Here, we estimate 1 / 0 Ϸ 10 12 to be consistent with previous work. For the device that received the N 2 post-gate-oxidation anneal ͑sample C, t ox =48 nm͒, we find N bt Ϸ 1.5ϫ 10 11 cm −2 in 1989 and N bt Ϸ 4.5ϫ 10 10 cm −2 in 2007.…”
supporting
confidence: 90%
“…[8][9][10][11][12][13] Here, we estimate 1 / 0 Ϸ 10 12 to be consistent with previous work. For the device that received the N 2 post-gate-oxidation anneal ͑sample C, t ox =48 nm͒, we find N bt Ϸ 1.5ϫ 10 11 cm −2 in 1989 and N bt Ϸ 4.5ϫ 10 10 cm −2 in 2007.…”
supporting
confidence: 90%
“…The flicker 1/f noise in semiconductors and metals is usually associated with structural defects. Therefore, introduction of defects by electron, ion, gamma or X-ray irradiation normally results in increased levels of 1/f noise [2,[18][19][20]. However, as an exception to the rule, there have been a few reports when the 1/f noise decreased as a result of irradiation [24][25].…”
mentioning
confidence: 99%
“…Meisenheimer and Fleetwood [18] found that the magnitude of the noise in N-channel integrated MOSFETs correlates with the amount of radiation-induced positive oxide-trapped charge present during irradiation and anneal, but noise magnitude did not correlate with the interface-trapped charge. A correlation between pre-irradiation llfnoise and radiation hardness has also been reported [19], and it was found that the magnitude of the llf noise present in an MOS device is correlated with the radiation-induced hole-trapping efficiency of the oxide [20]. The physical reasons for that correlation have been attributed to the simple oxygen vacancy near the Si/SiO2 interface known to be present in the Si02 before irradiation.…”
Section: -mentioning
confidence: 74%